EMPLOYMENT GROWTH IN RURAL INDIA: DISTRESS DRIVEN? - Vinoj Abraham (Centre for Development Studies-WP404, 2002)
The 61st round of NSS shows that there is a turnaround in employment growth in rural India after a phase of `jobless growth'. Paradoxically, this employment growth occurred during a period of wide spread distress in agriculture sector that include low productivity, price instability and stagnation leading to indebtedness. Under the typicalneoclassical tradition, this trend would have predicted further contraction of employment in the rural economy. However, further probing reveals that employment growth in the rural areas is probably a response to the crisis that is gripping the agriculture sector. Under conditions of distress, when income levels fall below sustenance then that part of the normally non-working population are forced to enter the labour market to supplement the household income. The decline of agricultural sector has also probably created forced sectoral and regional mobility of the normally working population with the normally non-working population complementing them.